External approach to frontal sinus mucocele: A forgotten technique? - Fernando Milhazes; Daniel Miranda; António Fontes Lima; Filipa Carvalho Moreira; Isabel Costa; Cátia Azevedo; Miguel Quintas-Neves; Luís Dias (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
Frontal sinus mucoceles are benign, slow growing lesions capable of local bone erosion. Currently, endoscopic sinus surgery is the mainstay for its treatment, however there are still indications for an external surgical approach. Here, we focus on the indications for an external surgical approach for frontal sinus mucocele treatment. To do so, we review the patients with frontal sinus mucocele treated by this approach in Hospital de Braga from 2012 to 2019.